Transcendence and Immanence: Teacher Professionalism in Islamic Religious Perspectives - Soufian Hady (Nadwa: Jurnal Pendidikan Islam, 2019)
The purpose of this research is to describe what is essence of professionalism teacher in Islamic perspective. This research uses library research. The results showed that the professionalism of teachers in Islam is based on two basic criteria, namely a call of life (Abdullah; transcendence) and expertise (khalifatullah; immanence). Therefore, the Professional teachers in Islam have the dual task of being carriers of religious (trancendence) and scientific missions (immanence). The first mission of professional teacher is to convey the da'wah and values of religious teachings to students, so students can live their lives in accordance with religious norms and have an awareness that all their actions are worthy of pure worship only for their Lord. While the second mission (immanence) of a teacher is to bring students to be intelligent student and master the latest knowledge according to students' interests. Hopefully this idea can be the spirit of future teacher professional development such as the implementation of Teacher Professional Education (TPE / PPG).Keywords: transcendence; immanence: teacher professionalism; Islamic religious; Teacher Professional Education; TPE AbstrakTujuan penelitian ini adalah untuk mendeskripsikan esensi profesionalisme dalam perspektif Islam. Metode penelitian menggunakan studi kepustakaan. Hasil penelitian menunjukkan bahwa profesionalisme guru dalam Islam pada dasarnya didasarkan pada dua kriteria dasar, yaitu panggilan hidup (transendensi Abdillah) dan keahlian (khalifatullah immanence). Oleh karena itu, para guru profesional dalam Islam memiliki tugas ganda yaitu menjadi pembawa misi keagamaan (trancendence) dan misi ilmiah (imanensi). Misi pertama guru profesional adalah untuk menyampaikan dakwah dan nilai-nilai ajaran agama kepada siswa, sehingga siswa dapat menjalani kehidupan mereka sesuai dengan norma-norma agama dan memiliki kesadaran bahwa semua tindakan mereka layak ibadah murni hanya untuk Tuhan mereka. Sedangkan misi kedua (imanensi) seorang guru adalah membawa siswa menjadi siswa yang cerdas dan menguasai pengetahuan terbaru sesuai dengan minat siswa.Kiranya hal ini bisa menjadi semangat pengembangan profesi guru mendatang seperti pelaksanaan Pendidikan Profesi Guru (PPG).Kata Kunci: transendensi; imanensi: profesionalisme guru; agam Islam; Pendidikan Profesi Guru (PPG)